2017
DOI: 10.1136/bjophthalmol-2016-309790
|View full text |Cite
|
Sign up to set email alerts
|

Retinal structure assessed by OCT as a biomarker of brain development in children born small for gestational age

Abstract: SGA children, both preterm and term born, showed evidence of structural abnormalities in the retina, which may be an accurate and non-invasive biomarker of neuronal damage in brain tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
2
10
0
1
Order By: Relevance
“…These results are consistent with those found in two previous studies, where preterm infants who were SGA had thinner GCL‐IPL and mRNFL (Pueyo et al. 2015, 2017). In our study, we observed that the 33–34 weekers, who were included for weighing less than 1500 g at birth and were all SGA, presented a reduction in total mRNFL, but not in GCL‐IPL thickness, associated with lower birth weight.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are consistent with those found in two previous studies, where preterm infants who were SGA had thinner GCL‐IPL and mRNFL (Pueyo et al. 2015, 2017). In our study, we observed that the 33–34 weekers, who were included for weighing less than 1500 g at birth and were all SGA, presented a reduction in total mRNFL, but not in GCL‐IPL thickness, associated with lower birth weight.…”
Section: Discussionsupporting
confidence: 93%
“…The association between GCL-IPL thickness and prematurity is controversial. Some studies report thicker GCL-IPL in preterm children (Yanni et 2012;Raffa et al 2016), whereas others report thinner GCL-IPL in preterm children (Pueyo et al 2015(Pueyo et al , 2017Fieß et al 2017). Similar observations can be made for mRNFL, with no difference in some studies (Raffa et al 2016) and thickening (Balasubramanian et al 2019) and thinning (Pueyo et al 2015) in preterm children in others.…”
Section: Visual Acuity Mean (Sd) Rangesupporting
confidence: 57%
See 1 more Smart Citation
“…Previous studies using magnetic resonance imaging (MRI) have reported changes in brain reorganization in small fetuses, demonstrated by differences in regional volumes 17 , brain metabolism 18 and connectivity 19 . In particular, we demonstrated previously significant differences in cortical development and the corpus callosum on MRI in late-onset small fetuses.…”
Section: Introductionmentioning
confidence: 99%
“…Esta técnica de imagen ya ha sido utilizada para estudiar otras enfermedades neurodegenerativas, como la esclerosis múltiple o el Alzheimer 13,14 . Pueyo et al 30 demostraron la utilidad del análisis de CCG mediante OCT como marcador de daño neuronal en niños con crecimiento intrauterino retardado, lo cual resulta coherente con nuestros resultados, puesto que todos los niños expuestos a tóxicos -tanto drogas de abuso como tabaco y alcoholmostraron una reducción significativa de la CCG. Por lo tanto, la OCT parece ser una herramienta útil en el estudio de un posible daño perinatal, como en este caso es la exposición prenatal a tóxicos.…”
Section: Discussionunclassified